2009
DOI: 10.1038/emboj.2009.123
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 acetylation at prometaphase is required for modulating APC/C activity and timing of mitosis

Abstract: Regulation of BubR1 is central to the control of APC/C activity. We have found that BubR1 forms a complex with PCAF and is acetylated at lysine 250. Using mass spectrometry and acetylated BubR1-specific antibodies, we have confirmed that BubR1 acetylation occurs at prometaphase. Importantly, BubR1 acetylation was required for checkpoint function, through the inhibition of ubiquitin-dependent BubR1 degradation. BubR1 degradation began before the onset of anaphase. It was noted that the pre-anaphase degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 49 publications
4
153
0
Order By: Relevance
“…Substitution of lysine (K) with a glutamine (Q) mimics an acetylated amino acid state, while substitution with an arginine (R) mimics deacetylation (Choi et al., 2009). Immunoblotting verified that exogenous BubR1 protein was efficiently overexpressed in mouse oocytes (Figure 2a–b), and the various mutant BubR1 proteins were expressed to the similar extent (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substitution of lysine (K) with a glutamine (Q) mimics an acetylated amino acid state, while substitution with an arginine (R) mimics deacetylation (Choi et al., 2009). Immunoblotting verified that exogenous BubR1 protein was efficiently overexpressed in mouse oocytes (Figure 2a–b), and the various mutant BubR1 proteins were expressed to the similar extent (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, BubR1 was identified to be acetylated at K250 at prometaphase in human cells. Chromosome segregation in cells expressing BubR1‐K250Q was delayed, whereas mitotic progression was accelerated in cells expressing BubR1‐K250R (Choi et al., 2009). Loss of BubR1 acetylation causes defects in SAC signaling and promotes tumor formation in mice (Park et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that BubR1 degradation occurs prior to mitotic exit. [39][40][41] The decline in total BubR1 occurs in the similar time frame as the decrease in levels of H3S10Ph.…”
Section: Belinostat Curtails Vincristine-induced Sac Activation and Cmentioning
confidence: 87%
“…Cdc20 is an activating cofactor of APC/C during mitosis (8); an active mitotic checkpoint inhibits APC/C through APC/C-dependent polyubiquitylation of Cdc20 and subsequent degradation by the proteasome (12). BubR1 binds to and inhibits both Cdc20 (13) and APC/C itself (14), acting as a pseudosubstrate inhibitor that, depending on acetylation status, can be actively degraded by APC/C Cdc20 (15). The role of Bub3 in the MCC is unclear, although in fission yeast it is involved in MCC localization (16).…”
Section: Introductionmentioning
confidence: 99%